Dietary Patterns, Physical Activity, and Nutritional Status among Adolescents in Tahfidzul Qur'an Klinterejo Sooko Boarding School in Indonesia - Maskhuriyah, Uus Eka; Kumalasari, Mei lina Fitri; Nilandita, Widya (International Conference on Sustainable Health Promotion, 2025)
A balanced diet and physical activity are important for maintaining physical health because both affect the body's energy balance and metabolism. An improper diet and lack of physical activity can affect nutritional status, both malnutrition and overnutrition. This study aims to determine whether there is a relationship between diet and physical activity and the nutritional status of adolescents. The research design used was a cross-sectional study with a sample size of 85 people. The data collected included age characteristics, dietary patterns, physical activity, and nutritional status. Dietary patterns were measured using a FFQ instrument, physical activity was measured using a questionnaire, and nutritional status was measured using anthropometry. The sampling method used was random sampling, and the researchers determined the normality of the sample using Spearman's rank correlation test to determine the relationship between the two variables. The results of the study showed that dietary patterns were related to nutritional status in children with a p-value of 0.001. There was a relationship between physical activity and nutritional status in children with a p-value of 0.010. The conclusion of this study is that there is a relationship between dietary patterns, physical activity, and nutritional status